The Semiotic Meaning Of The Giant Statue of Mazu And The Place On Meizhou Island Of China (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article briefly describes the geographical environment of Meizhou Island, analyzes theorigin and aesthetic characteristics of the giant statue of Mazu, and focuses on its semioticmeaning from the perspective of the giant statue of Mazu as a visual image resource, it hasfunction of education, this is conducive to develop Mazu culture.